Odpowiedź:
[tex]2.10\\\\W(x)=-x^3+2x^2-x+5\ \ \ \ ,\ \ P(x)=2x^2-x+1\ \ \ \ ,\ \ Q(x)=5x+2\\\\\\a)\ \ 2W(x)+3P(x)-Q(x)\\\\2(-x^3+2x^2-x+5)+3(2x^2-x+1)-(5x+2)=\\\\=-2x^3+4x^2-2x+10+6x^2-3x+3-5x-2=-2x^3+10x^2-10x+11\\\\\\b)\ \ 2[W(x)-P(x)]+Q(x)\\\\2(-x^3+2x^2-x+5-(2x^2-x+1))+5x+2=\\\\=2(-x^3+2x^2-x+5-2x^2+x-1)+5x+2=2(-x^3+4)+5x+2=\\\\=-2x^3+8+5x+2=-2x^3+5x+10[/tex]
[tex]c)\ \ W(x)-[P(x)+3Q(x)]\\\\-x^3+2x^2-x+5-(2x^2-x+1+3(5x+2))=\\\\=-x^3+2x^2-x+5-(2x^2-x+1+15x+6)=-x^3+2x^2-x+5-(2x^2+14x+7)=\\\\=-x^3+2x^2-x+5-2x^2-14x-7=-x^3-15x-2[/tex]